Pantun-Based Cognitive Activation And Local Inquiry: Enhancing Mathematical Critical Thinking Through Bilah Panai Cultural Practices - Endi Zunaedy Pasaribu; Mesra Wati Ritonga; Zul Amry; Edy Surya (Tsaqila | Jurnal Pendidikan dan Teknologi, 2026)
Mathematical critical thinking is a fundamental competency in mathematics education; however, instructional practices often provide limited opportunities for students to engage in reasoning, inquiry, and reflective thinking. While ethnomathematics has been increasingly integrated into mathematics learning, most studies emphasize cultural artifacts as contextual resources rather than cultural practices as mechanisms of thinking. This study explores the role of Bilah Panai cultural practices, namely pantun and merisik/telangkai, in enhancing students’ mathematical critical thinking skills. Pantun was implemented as a cognitive activation strategy to stimulate prior knowledge and interpretation, whereas merisik/telangkai was adapted as a local inquiry process that encouraged investigation, discussion, argumentation, and collaborative problem solving. The study involved Grade 10 students participating in mathematics learning activities grounded in Bilah Panai cultural practices. Data were collected through classroom observations, students’ mathematical critical thinking assessments, and learning activity documentation. The findings indicate that pantun supported students in identifying mathematical ideas and constructing initial interpretations, while merisik/telangkai facilitated reasoning, analysis, and problem-solving processes. These cultural practices created meaningful learning experiences and promoted active engagement in mathematical inquiry. The study highlights the potential of local cultural practices to function not merely as learning contexts but as cognitive and inquiry mechanisms that support the development of mathematical critical thinking. This finding contributes to the advancement of ethnomathematics and culturally responsive mathematics education. Quantitative findings showed an improvement in students’ mathematical critical thinking scores from a mean pretest score of 58.60 to a mean posttest score of 88.20, yielding a high normalized gain score (g = 0.715). Keywords: Mathematical Critical Thinking; Ethnomathematics; Bilah Panai Culture; Pantun; Local Inquiry; Culturally Responsive Mathematics Education.